2004
DOI: 10.1111/j.1741-1130.2004.04031.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Self‐Determination Theory to Japanese Special Education Contexts: A Four‐Step Model

Abstract: The authors describe what preparations they undertook before introducing self‐determination theory and its corresponding teaching model to the Japanese special education system for students with intellectual disabilities. The Japanese special education services are designed to nurture students to be individuals who are independent, know and exhibit preferences and interests, set and achieve goals, and possess a sense of achievement and self‐awareness. In this respect, the values embedded in the practices of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Shogren (2011) explored the literature on culture and the fSDT, and found theoretical and empirical research examining the expression of self-determined behaviour in Diné cultures (Navajo) (Frankland, Turnbull, Wehmeyer, & Blackmountain, 2004), Korean (Lee & Wehmeyer, 2004), Japanese (Ohtake & Wehmeyer, 2004), Chinese (Zhang, Wehmeyer, & Chen, 2005), as well as diverse cultures within the United States (Trainor, 2005;Valenzuela & Martin, 2005). Researchers in Italy (Nota, Ferrari, Soresi, & Wehmeyer, 2007) and Belgium (Lachapelle et al, 2005) have also explored self-determination and its relationship with other constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Shogren (2011) explored the literature on culture and the fSDT, and found theoretical and empirical research examining the expression of self-determined behaviour in Diné cultures (Navajo) (Frankland, Turnbull, Wehmeyer, & Blackmountain, 2004), Korean (Lee & Wehmeyer, 2004), Japanese (Ohtake & Wehmeyer, 2004), Chinese (Zhang, Wehmeyer, & Chen, 2005), as well as diverse cultures within the United States (Trainor, 2005;Valenzuela & Martin, 2005). Researchers in Italy (Nota, Ferrari, Soresi, & Wehmeyer, 2007) and Belgium (Lachapelle et al, 2005) have also explored self-determination and its relationship with other constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lee and Wehmeyer (2004) found that Korean teachers have embraced self-determination practices well in their daily instruction. These and other studies (e.g., Ohtake & Wehmeyer, 2004) reveal that instructional practices promoting students' self-determination are widely accepted by many cultures and, therefore, self-determination instructional models can and should be applied to diverse cultures.…”
Section: Instructional Practices That Promote Student Self-determinationmentioning
confidence: 99%
“…The students involved in instruction from teachers using the model, including adolescents and young children with cognitive and developmental disabilities, were able to self-direct educational goal setting and attainment and to become more self-determined. The model was introduced to Japan and Korea (Lee & Wehmeyer, 2004;Ohtake & Wehmeyer, 2004) and was found to work well in these cultures. This may lead to consideration by other cultures.…”
Section: Modelsmentioning
confidence: 99%
See 2 more Smart Citations